Utilization of Smart Agricultural Technology to Improve Resource Efficiency in Agro-industry - Zulfikhar, Rosa; Alaydrus, Ali Zainal Abidin; Sutiharni, Sutiharni; Nanjar, Agi; Hartati , Hartati (Westscience Press, 2024)
This study investigates the utilization of smart agricultural technologies to improve resource efficiency in the agro-industry, using a quantitative approach with a focus on Structural Equation Modeling - Partial Least Squares (SEM-PLS) analysis. A survey of 250 agro-industry stakeholders produced descriptive statistics showing a high mean adoption score (4.2) and a significant frequency of adoption (75%). Resource efficiency indicators, including average water use (32.5 gallons per hectare), average energy consumption (15.8 kWh per hectare), and average crop yield (2,800 kg per hectare), were also assessed. The SEM-PLS results showed strong reliability and validity of the measurement model, with positive path coefficients indicating substantial impacts of smart technology adoption on water use efficiency, energy consumption optimization, and crop yield. The model showed a satisfactory fit, and bootstrapping confirmed the robustness of the relationships. The discussion highlights practical implications for farmers, policymakers, and technology providers, emphasizing the potential for increased efficiency, reduced costs, and improved yields through the adoption of smart technologies. This study contributes valuable insights to the discourse of sustainable agricultural practices.